A Novel Prototype Neonatal Resuscitator That Controls Tidal Volume and Ventilation Rate: A Comparative Study of Mask Ventilation in a Newborn Manikin - Solevåg, Anne Lee; Haemmerle, Enrico; van Os, Sylvia; Bach, Katinka P.; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2016)
The objective of this randomized controlled manikin trial was to examine tidal volume (VT) delivery and ventilation rate during mask positive pressure ventilation (PPV) with five different devices, including a volume-controlled prototype Next StepTM device for neonatal resuscitation. We hypothesized that VT and rate would be closest to target with the Next StepTM. Twenty-five Neonatal Resuscitation Program (NRP) providers provided mask PPV to a newborn manikin (simulated weight 1kg) in a randomized order with: a self-inflating bag (SIB), a disposable T-piece, a non-disposable T-piece, a stand-alone resuscitation system T-piece, and the Next StepTM. All T-pieces used a peak inflation pressure of 20cmH2O and a positive end-expiratory pressure of 5cmH2O. The participants were instructed to deliver a 5mL/kg VT (rate 40-60min-1) for 1min with each device and each of three test lungs with increasing compliance of 0.5, 1.0 and 2.0mL/cmH2O. VT and ventilation rate were compared between devices and compliance levels (linear mixed model). All devices, except the Next StepTM delivered a too high VT, up to six-fold the target at the 2.0mL/cmH2O compliance. The Next StepTM VT was 26% lower than the target in the low compliance. The ventilation rate was within target with the Next StepTM and SIB, and slightly lower with the T-pieces. In conclusion, routinely used newborn resuscitators over delivered VT, whereas the Next StepTM under delivered in the low compliant test lung. The SIB had higher VT and rate than the T-pieces. More research is needed on volume-controlled delivery room ventilation.